2020
DOI: 10.3389/fmicb.2020.00372
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine Safety: Myths and Misinformation

Abstract: The World Health Organization has named vaccine hesitancy as one of the top ten threats to global health in 2019. The reasons why people choose not to vaccinate are complex, but lack of confidence in vaccine safety, driven by concerns about adverse events, has been identified as one of the key factors. Healthcare workers, especially those in primary care, remain key influencers on vaccine decisions. It is important, therefore, that they be supported by having easy access to trusted, evidencebased information o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
174
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(179 citation statements)
references
References 47 publications
2
174
1
2
Order By: Relevance
“…Approaches to the diagnosis of autism have historically lacked consistency (Geoghegan, O’Callaghan, and Offit 2020a , b ). A qualitative study conducted with 14 autistic women found that their late diagnosis was often because doctors and educators mistakenly believed that autism is a male condition, therefore missing the signs of autism in females (Bargiela, Steward, and Mandy 2016 ).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Approaches to the diagnosis of autism have historically lacked consistency (Geoghegan, O’Callaghan, and Offit 2020a , b ). A qualitative study conducted with 14 autistic women found that their late diagnosis was often because doctors and educators mistakenly believed that autism is a male condition, therefore missing the signs of autism in females (Bargiela, Steward, and Mandy 2016 ).…”
mentioning
confidence: 99%
“…The Australian government has recently announced a new national standard for the diagnosis of autism in Australia that aims to address the lack of consistency in diagnosis of autism. The guidelines adopt a person-centered approach, which emphasise listening to individuals and their families about their strengths and needs (Geoghegan, O’Callaghan, and Offit 2020a , b ). Early, timely, and accurate identification and diagnosis is critical to ensure that autistic people receive appropriate support services.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond concerns specific to influenza vaccine, more generalized concerns may influence decisions to vaccinate. Concerns over safety and vaccine ingredients, number of vaccines administered, mistrust of the mainstream medical system, and the belief that vaccination should be a personal choice persist, and are often shaped by a parent's social sphere of influence [50][51][52][53].…”
Section: Limitationsmentioning
confidence: 99%
“…Presently, such vaccine hesitancy may be viewed as “abnormal”. Routine vaccinations are widely recognized as effective preventive interventions to reduce or eradicate viral illnesses, saving millions of lives throughout the world [ 1 ]. Since the beginning of the COVID-19 pandemic, a SARS-CoV-2 vaccine has been presented as the solution to exit the worldwide health, socio-political, and economic crises [ 2 , 3 ].…”
mentioning
confidence: 99%